2000
DOI: 10.1086/315195
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi–Induced Oxidative Burst, Calcium Mobilization, and Phagocytosis of Human Neutrophils Are Complement Dependent

Abstract: When Borrelia burgdorferi, the spirochete causing Lyme disease, is transmitted to a human, the complement system is among the first challenges facing the bacterium. Neutrophils are crucial leukocytes in the first line of host defense against bacterial infections. To investigate the role of complement in the Borrelia-induced activation of human neutrophils, oxidative burst, calcium mobilization, and phagocytosis induced by three subspecies of B. burgdorferi were studied. Each subspecies induced all observed neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
3
24
0
2
Order By: Relevance
“…Borrelia species incubated in vitro with serum have been shown to have divergent sensitivities to lysis by complement (7,25,49). We have further elucidated the role of complement in the host response to Borrelia infection by comparing the course of infection by B. burgdorferi B31 in mice genetically deficient in complement component C3 to that in mice with an intact complement system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borrelia species incubated in vitro with serum have been shown to have divergent sensitivities to lysis by complement (7,25,49). We have further elucidated the role of complement in the host response to Borrelia infection by comparing the course of infection by B. burgdorferi B31 in mice genetically deficient in complement component C3 to that in mice with an intact complement system.…”
Section: Discussionmentioning
confidence: 99%
“…Lyme disease Borrelia organisms have varied abilities to survive in the presence of complement in vitro. In general, B. afzelii is resistant, B. burgdorferi is partially resistant, and B. garinii is sensitive to killing by complement in normal human serum (7,25,49). Alitalo et al (1) have shown that, in vitro, B. afzelii and B. burgdorferi are able to bind the host complement regulatory proteins factor H and factor Hlike protein 1.…”
mentioning
confidence: 99%
“…5A and B), similar to what was observed for mouse macrophages. We also tested whether human neutrophil-like cells have a similar function, since neutrophil is another type of professional phagocyte that can avidly phagocytose B. burgdorferi (69,70). The result showed that uptake of the ospC mutant by human neutrophils was similar to that of the parental wild-type strain (Fig.…”
Section: Fig 3 the Ospc Mutant Disseminates And Colonizes F4/80mentioning
confidence: 97%
“…These findings are correlated with the susceptibility of these strains to complement-dependent phagocytosis in human serum (30). Our aim in this study was to determine whether bacterial control of the alternative complement pathway might contribute to the pathogenicity of B. burgdorferi s.l.…”
mentioning
confidence: 98%